2004
DOI: 10.1097/01.aog.0000130065.49187.c8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Benign Endometrial Masses by Endometrial Stripe Measurement in Premenopausal Women

Abstract: Using an endometrial stripe cutoff of 5 mm in premenopausal women would miss significant intracavitary pathology. The sonographic evaluation of abnormal uterine bleeding in premenopausal women should include sonohysterography or equivalently accurate testing regardless of endometrial stripe thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 14 publications
1
31
0
1
Order By: Relevance
“…For ideal imaging, the ultrasound equipment must be of adequate quality to display myometrial and endometrial features clearly, and the examiner must have the ability to operate the scanning device and interpret the images displayed. Even in ideal circumstances, TVUS is not 100% sensitive because polyps and other small lesions may elude detection, even in the context of a normal study [61,62]. If good ultrasonic images are obtained and there is an absence of findings indicative of endometrial polyps or submucosal myomas, the endometrial cavity may presumptively be considered normal from the perspective of lesions causing or contributing to AUB.…”
Section: Evaluation Of the Structure Of The Endometrial Cavitymentioning
confidence: 99%
“…For ideal imaging, the ultrasound equipment must be of adequate quality to display myometrial and endometrial features clearly, and the examiner must have the ability to operate the scanning device and interpret the images displayed. Even in ideal circumstances, TVUS is not 100% sensitive because polyps and other small lesions may elude detection, even in the context of a normal study [61,62]. If good ultrasonic images are obtained and there is an absence of findings indicative of endometrial polyps or submucosal myomas, the endometrial cavity may presumptively be considered normal from the perspective of lesions causing or contributing to AUB.…”
Section: Evaluation Of the Structure Of The Endometrial Cavitymentioning
confidence: 99%
“…The normal menstrual cycle occurs over a span of 4.5 to 8 days every 24 to 38 days, with cycle-to-cycle variation over 12 months of ± 2 to 20 days. 4 Cycle length varies most during the years immediately succeeding menarche (age <20 years) and during the perimenopausal transition (age >40 years), as these age ranges have the highest prevalence of anovulatory cycles.…”
Section: The Normal Menstrual Cyclementioning
confidence: 99%
“…However, it is important to remember that 1out of 6 intracavitary lesions can be missed on TVS in women with AUB. Therefore, we believe that when it is possible to perform SIS instead of TVS 23 given its higher sensitivity in detecting submucosal myomas and endometrial polyps in premenopausal women 24. If SIS is not available, we believe that a diagnostic hysteroscopy should be considered if available.…”
mentioning
confidence: 99%
“…TVUS is also minimally invasive and widely acceptable to women, and it helps triage women requiring further treatment. The sensitivity and specificity of TVUS for the detection of fibroids and polyps alongside ET are 80% and 69%, respectively [17]. Therefore, to prevent endometrial lesions from being missed, it is increasingly being suggested that hysteroscopy or SIS is recommended to further evaluate the endometrium [18].…”
Section: Pelvic Tvusmentioning
confidence: 99%